2004
DOI: 10.1109/led.2004.831190
|View full text |Cite
|
Sign up to set email alerts
|

12 W/mm AlGaN–GaN HFETs on Silicon Substrates

Abstract: Al 0 26 Ga 0 74 N-GaN heterojunction field-effect transistors were grown by metal-organic chemical vapor deposition on high-resistivity 100-mm Si (111) substrates. Van der Pauw sheet resistance of the two-dimensional electron gas was 300 square with a standard deviation of 10 square.Maximum drain current density of 1 A/mm was achieved with a three-terminal breakdown voltage of 200 V. The cutoff frequency and maximum frequency of oscillation were 18 and 31 GHz, respectively, for 0.7-m gate-length devices. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(118 citation statements)
references
References 10 publications
6
112
0
Order By: Relevance
“…[1][2][3][4] Epitaxial AlGaN/GaN heterostructure forms two-dimensional electron gas (2DEG) at the interface due to the unique polarization properties of III-Nitride materials. 5,6 The spontaneous polarization and piezoelectric polarizations play an important role in the formation of 2DEG at the AlGaN/GaN interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Epitaxial AlGaN/GaN heterostructure forms two-dimensional electron gas (2DEG) at the interface due to the unique polarization properties of III-Nitride materials. 5,6 The spontaneous polarization and piezoelectric polarizations play an important role in the formation of 2DEG at the AlGaN/GaN interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The O + ion implant isolation was also investigated on AlGaAs [9], InAlN [10], and GaN (n-type doping)/GaN materials [11] to study the isolation quality, and P/He, Ar + , and N + ions have been employed in AlGaN/GaN HEMTs [12]- [14].…”
mentioning
confidence: 99%
“…It has to be noted that 0.25 mm devices with a FP-extension of 0.5µm towards the drain contact, i.e. their extension towards the drain is 0.25µm longer than the extension of the top of the T-gates, yield a [1,3,[10][11][12][13]. It can be concluded that we have achieved state-of-the-art results with respect to the generation of large, i.e.…”
Section: Large-periphery Devicesmentioning
confidence: 96%